The Increased Expression of an Engrailed to Sustain Shell Formation in Response to Ocean Acidification - Zhang, Yukun; Liu, Zhaoqun; Zong, Yanan; Zheng, Yan; Li, Yinan; Han, Zirong; Wang, Lingling; Song, Linsheng (Frontiers in Physiology, 2020)
The engrailed gene is a transcription factor required in numerous species for important developmental steps such as neurogenesis, segment formation, preblastoderm organization and compartment formation. Recent study has proved that engrailed is also a key gene related to shell formation in marine bivalves. In the present study, the expression patterns of an engrailed gene (Cgengrailed-1) in Pacific oyster Crassostrea gigas under CO2-driven acidification were investigated to understand its possible role in the regulation of shell formation and adaptation to ocean acidification (OA). The open reading frame (ORF) of Cgengrailed-1 was identified from C. gigas, which was of 690 bp encoding a polypeptide of 230 amino acids with a HOX domain. Phylogenetic analysis indicated that the deduced amino acid sequence of Cgengrailed-1 shared high homology with other engrailed proteins from Drosophila melanogaster, Mizuhopecten yessoensi and Crassostrea virginica. The expression level of Cgengrailed-1 mRNA in adult oyster’s mantle decreased after moderate (pH 7.8) and severe (pH 7.4) acidification treatment (0.75- and 0.15-fold of that in control group, p < 0.05), and the protein expression of Cgengrailed-1 in the middle fold of mantle tissue increased significantly in moderate acidification treatment group. As for larval oyster from trochophore to D-shape larvae stages, the expression levels of Cgengrailed-1 mRNA showed a slight increase in both moderate acidification treatment and severe acidification treatment, which was 1.10- and 1.20-fold of that in control group (p < 0.05). The whole-mount immunofluorescence assay revealed that the positive signals of Cgengrailed-1 were observed on the margin of shell gland and periostracum in trochophore, early D-shape larvae and D-shape larvae in both control and acidification groups, and the intensity of positive signals increased dramatically along with the increase of acidification intensity. These results collectively suggested that the expression of Cgengrailed-1 could be triggered by CO2-driven acidification treatment, which might contribute to regulate the shell formation in oyster larvae and the formation of periostracum shell in adult oyster in future OA environment.